Concentrations of polycyclic aromatic hydrocarbons in Antarctic snow polluted by research activities using snow mobiles and diesel electric generators - Thi, Hien TO; KAWAMURA, Kenji; Kim, Oanh PHAM; TANIGUCHI, Tatsuya; NORO, Kazushi; TAKENAKA, Norimichi; ARAI, Miho; FUJII, Yusuke; MOTOYAMA, Hideaki; SAKURAI, Toshimitsu; NABESHIMA, Yoshie (Bulletin of Glaciological Research, 2019)
The polycyclic aromatic hydrocarbons (PAHs) in snow were measured in eastern Dronning Maud Land, East Antarctica. The sources of these PAHs were the snow mobiles and diesel electric generators used for scientific research from 29th December 2015 to 4th February 2016. Most of the measured PAH concentrations were low before the research campaign (lower than the detection limit or quantification limit), then increased due to the research activities, and finally decreased to a low level (lower than the quantification limit), probably because of strong blizzard winds. In addition, photolysis of the PAHs in the polluted snow samples under Antarctic conditions was investigated. The snow samples polluted by diesel electric generators were collected before and after irradiation under Antarctic sunlight (11 days); however, a decrease in PAH concentration was not observed. It was concluded that photolysis was not the main sink of the PAHs in Antarctic snow, but the occurrence of blizzard/drifting snow decreased the PAH concentration. In this paper, the preservation method for the snow samples to measure the PAHs correctly was also evaluated. To stabilize the PAHs in snow, hexane had to be added to the snow sample. Even if the snow sample was kept in a freezer, PAHs evaporated without hexane.